Diet-disease relationships: Recent advances in nutritional epidemiology - Raul Zamora-Ros; Carlos Alberto González (Mètode Science Studies Journal: Annual Review)
Nutritional epidemiology currently studies the diet-disease relationships. In order to evaluate these associations, an accurate estimation of nutritional exposure is essential. Traditional dietary questionnaires are being complemented with the measurement of nutritional biomarkers. New methodologies, including the use of new dietary assessments, metabolomics for increasing the quantity and quality of biomarkers, and statistical approaches to combine both techniques, are required to move forward in this field. In this review, we have selected five of the more relevant accomplishments in this field as examples of the importance of dietary factors in the prevention of non-communicable diseases. This theoretical knowledge needs to be finally translated by public health experts into dietary recommendations to the general population.